If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2b + 10 = b + 4 Reorder the terms: 10 + 2b = b + 4 Reorder the terms: 10 + 2b = 4 + b Solving 10 + 2b = 4 + b Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-1b' to each side of the equation. 10 + 2b + -1b = 4 + b + -1b Combine like terms: 2b + -1b = 1b 10 + 1b = 4 + b + -1b Combine like terms: b + -1b = 0 10 + 1b = 4 + 0 10 + 1b = 4 Add '-10' to each side of the equation. 10 + -10 + 1b = 4 + -10 Combine like terms: 10 + -10 = 0 0 + 1b = 4 + -10 1b = 4 + -10 Combine like terms: 4 + -10 = -6 1b = -6 Divide each side by '1'. b = -6 Simplifying b = -6
| 9-10x-5-4x=6 | | 10c^2+33c-54=0 | | A^5*6a^3=y | | 5x^0y^1= | | (x+1)+(x-1)=e^4 | | .5(10-9x)=1.25 | | .5(10-9x)=.125 | | 8c-1200=5c | | 56765x+68-79=9865 | | 9-17x-5-4x=7 | | -x-8+14x=34 | | 3x+1y=21 | | 4-0.9k=4 | | 1x+2y=12 | | 3n^2-8n+5= | | -4(5+7y)+6(2y-9)= | | 33x^2-79x+40=0 | | -4(8-9x)= | | 49x^2-21x+2=0 | | X+3y-4=0 | | -4x+6y=-2 | | 3x+x=40 | | -9(5-3x)=9 | | 8(3n+7)-10n= | | 4k+-14+3k=21 | | 67x+45=67 | | -6(3y+5)= | | 6x+0.6=7x | | 2(v-5)=-(3v+5) | | (4*x)-6=(x*2)+4 | | 5m+7m=-4m | | 5(4n-3)= |